An assessment of micro-credentials in New Zealand vocational education. (2nd September 2022) - Fisher, Richard M.; Leder, Harry
ABSTRACT: In 2018, the New Zealand Qualifications Authority amended its regulatory framework in order to formally recognise micro-credentials. The rules provide a definition, credit value limits, and permission to publish on the NZQA website. The rules apply to Tertiary Education Organisations, leaving universities to establish their own micro-credential recognition schemes. There is provision in the rules for international providers, and non-TEO providers working within New Zealand, to seek equivalency for other micro-credentials. A non-doctrinal policy law framework was adopted to assess the adoption of micro-credentials by the NZQA. It included establishing a timeline of vocational education reform, reviewing currently registered micro-credentials, and identifying unresolved issues that may impact upon their future uptake in New Zealand. They include concerns about disaggregation of qualifications, avoidance of unnecessary replication of learning, and managing expectations about the future recognition and valuation of micro-credentials.